1989
DOI: 10.1002/neu.480200806
|View full text |Cite
|
Sign up to set email alerts
|

Aminergic cellular organization in the gills of Aplysia species

Abstract: The constituent elements of the gills of Aplysia kurodai and A. juliana were examined for the presence of biogenic amines using histochemical, immunocytochemical, and HPLC techniques. Aminergic elements were revealed by glyoxylic acid-induced fluorescence in the branchial nerve, branchial ganglion, branchial vessels, and pinnules in both species. Three types of fluorescent cells were found in the neural plexus of the gill in each species. Two of them might be sensory neurons. Although HPLC analysis showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For localizing GABA-like immunoreactive neural processes, methods previously described (Kurokawa et al 1989) were used with modifications in fixation according to Kuwasawa et al (1992). Paraffin serial sections were cut at a thickness of 10-15 lam.…”
Section: Methodsmentioning
confidence: 99%
“…For localizing GABA-like immunoreactive neural processes, methods previously described (Kurokawa et al 1989) were used with modifications in fixation according to Kuwasawa et al (1992). Paraffin serial sections were cut at a thickness of 10-15 lam.…”
Section: Methodsmentioning
confidence: 99%
“…The aforementioned dissected preparations were immersed in 4% carbodiimide [1-ethyl-3(3-dimethylaminopropyl)-carbodiimide] (Dojin-Wako) in PB for 1 h at room temperature, 4% paraformaldehyde in PB for 2-3 h, and rinsed in PB at 4°C. After washing with 0.1% PBT, preparations were treated using the peroxidase-antiperoxidase (PAP) method and stained with 3,3′-diaminobenzidine tetrahydrochloride (DAB; Kurokawa et al 1989), or double stained using fluorescein isothiocyanate (FITC) and tetrarhodamine isothiocyanate (TRITC) procedures. To detect serotonin and GABA, preparations were fixed with 4% paraformaldehyde in PB for 2-3 h. Fixed preparations were embedded in paraffin and sectioned one by one serially with a microtome at 3 µm, 5 µm, or 10 µm thickness.…”
Section: Immunocytochemical Studymentioning
confidence: 99%
“…Our data, in con trast, suggest that in the cat, as in the rat, the expression of TH-IR in these sensory neurons reflects the capacity to synthesize CA, in par ticular DA. The existence of dopaminergic sensory neurons has already been reported for other sensory systems [30,31], Of course, the existence of dopaminergic vasomotor fibers, as described in other structures [25][26][27][28][32][33][34], also remains a possibility, but our bio chemical data from sympathectomized ani mals would indicate that if such autonomic dopaminergic fibers are present in the CSN, they do not originate from the SCG. Further more, our histological studies demonstrated no appreciable loss of axonal TH-IR following sympathectomy, although changes in the inci dence of very small caliber TH-positive post ganglionic elements cannot reliably be ascer tained utilizing the present immunocytochemical, light-microscopic techniques.…”
Section: Discussionmentioning
confidence: 80%
“…At the peripheral terminus of the sensory fiber, release of DA could be expected to act on DA autoreceptors present on the type I cells [39,40], much as the peripheral release of substance P from sensory nerve endings has been demonstrated to have an important physiological role in other sensory systems [41,42], In support of this possibility, Finley et al [14] recently reported the ultrastructural localization of TH-positive unmyelinated fi bers in contact with type I cells in sympathec tomized carotid bodies in the rat. A role for DA might also need to be considered in the central processing of chemoreceptor informa tion transmitted by CSN fibers, as has also been proposed for this CA in other sensory pathways [30,31 ].…”
Section: Discussionmentioning
confidence: 99%